SELF-DIRECTED LEARNING AS A TOOL FOR STUDENTS’ MASTERY OF PHARMACEUTICAL MANAGEMENT AND THE LEGAL FOUNDATIONS OF PROFESSIONAL PRACTICEE - Садогурська, Катерина; Грешко, Юлія; Басараба, Роксолана (SWorldJournal, 2025)
The article examines the role of student independent work as an effective tool for mastering the content of the disciplines Pharmaceutical Management and Marketing, Pharmaceutical Law, and Introduction to Pharmacy. The significance of self-directed learni